2005
DOI: 10.1603/0022-0493-98.2.299
|View full text |Cite
|
Sign up to set email alerts
|

DNA Diagnostics to Identify Internal Feeders (Lepidoptera: Tortricidae) of Pome Fruits of Quarantine Importance

Abstract: A diagnostic polymerase chain reaction (PCR) method is presented for differentiating among the North American internal apple-feeding pests codling moth, Cydia pomonella (L.); oriental fruit moth, Grapholita molesta (Busck); lesser appleworm, Grapholita prunivora (Walsh); and cherry fruitworm, Grapholita packardi Zeller. An approximately 470-bp fragment of mitochondrial cytochrome oxidase subunit I (COI) was sequenced in three to six specimens of each species. Consistent and diagnostic differences were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The oriental fruit moth is a major pest of stone and pome fruit in many fruit‐growing regions of the world (Il'ichev et al., ; Natale et al., ; Barcenas et al., ; Myers et al., ; Chen & Dorn, ). It can produce 3–7 generations per year depending on the latitude or elevation (Barnes, ).…”
Section: Introductionmentioning
confidence: 99%
“…The oriental fruit moth is a major pest of stone and pome fruit in many fruit‐growing regions of the world (Il'ichev et al., ; Natale et al., ; Barcenas et al., ; Myers et al., ; Chen & Dorn, ). It can produce 3–7 generations per year depending on the latitude or elevation (Barnes, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DNA sequencing involves additional cost and time for quarantine work. Some recent studies have suggested that PCR with species-specific primers could overcome the need of DNA sequencing and accelerate the process of identification (Barcenas et al 2005;Rugman-Jones et al 2009;Zhang et al 2012;Jiang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Yvon et al (2009) discriminated virus variants and showed that HRM and standard melt results were 100% identical for c. 450 samples. Standard melt peak analysis has also been used to discriminate mammalian carnivores (Berry & Sarre 2007), insect quarantine pests (Barcenas, Unruh, & Neven 2005;Yu et al 2005) and fungi (Hsu et al 2003). However, with each of these analyses, different primer sets were used to amplify each of the known haplotypes within the populations under study.…”
Section: Introductionmentioning
confidence: 99%